Determining The Impact of Government Spending on Unemployment Levels In Syria During The Period 1990-2011 (An Econometric Study) - محلا, رباب; وليد عامر , (Latakia University Journal - Economic and Legal Sciences Series, 2023)
The study aims to determine the impact of government spending on unemployment levels in Syria during the period 1990-2011, in long and short terms, where annual data were used, represented by unemployment levels, government spending and gross domestic product at constant 2000 prices.. The Autoregressive Distributed Lag Models ARDL was used for Econometric Study. The study concluded that an equilibrium relationship was found between unemployment levels and other variables. The value of the correction coefficient was -1.98 , which is a negative and significant., i.e. the imbalances that may occur in short term can be corrected and returned to the equilibrium in the long term. The study also concluded that there is a positive and weak relationship between levels of government spending and levels of unemployment, which means the impact of government spending during the studied period was not positive in the context of reducing unemployment levels, which requires a review of the applied spending policy to achieve the desired goals.